Firm's strategies of innovation and the effect of economic crisis - Sérgio Nunes; Raul Lopes (European Regional Science Association (ERSA), 2013)
The economic and financial crisis has brought firms, territories and countries before a set of restrictions to a greater or lesser extent, function as the conditioners of economic activity for several agents, also affecting their activities associated with the development of its innovation process. Innovation is a highly complex process, very contingent and onerously demanding. With innovation as a key source of high economic performance, it is important to understand to what extent the current economic crisis is to constrain the innovation of firms and thus, the process of wealth creation. The main objective of this paper is to show that the economic crisis has a different effect on firms, depending on the type of innovation strategies adopted. For this, we identify some relevant relations between the economic crisis and the critical factors of the innovation process, namely knowledge networks and context costs, special dimensions that we associate with the efficiency of institutional and relational capital. These objectives will be achieved using several statistical and econometric techniques, with information found in a database obtained through a business survey. Our main results show some interesting findings: first we find evidence that the most dynamic firms recognize less impact of the economic crisis. Second, we find empirical evidence that the knowledge networks can be taken as a resilient mechanism of firms to manage the negative impacts of the crisis. Finally, firms that recognize more importance to the reduction of context cost seems more resilient to economic crisis. We finish with some recommendations for regional policy.
Keywords: 330; knowledge networks; innovation process; economic crisis; context costs; territorial resilience; regional policy